A quantitative review of the effects of Se application on the reduction of Hg concentration in plant: a meta-analysis - Chen, Jiefei; Hao, Shangyan; Bañuelos, Gary; Zhou, Xinbin (Frontiers in Plant Science, 2023)
Mercury (Hg) is a highly toxic heavy metal entering the human body through the food chain after absorption by plant. Exogenous selenium (Se) has been suggested as a potential solution to reduce Hg concentration in plants. However, the literature does not provide a consistent picture of the performance of Se on the accumulation of Hg in plant. To obtain a more conclusive answer on the interactions of Se and Hg, 1 193 data records were collected from 38 publications for this meta-analysis, and we tested the effects of different factors on Hg accumulation by meta-subgroup analysis and meta-regression model. The results highlighted both a significant dose-dependent effect of Se/Hg molar ratio on reduction of Hg concentration in plants, and the optimum condition for inhibiting Hg accumulation in plants is at Se/Hg ratio of 1-3. Exogenous Se significantly reduced Hg concentrations in the overall plant species, rice grains and non-rice species by 24.22%, 25.26% and 28.04%, respectively. Both Se(IV) and Se(VI) significantly reduced Hg accumulation in plants, but Se(VI) had a stronger inhibiting effect than that of Se(IV). Se significantly decreased the BAFGrian in rice, which indicated other physiological processes in rice may be involved in restricting uptake from soil to rice grain. Therefore, Se can effectively reduce Hg accumulation in rice grain, which provides a strategy for effectively alleviating the transfer of Hg to the human body through the food chain.